SOCIO-PSYCHOLOGICAL FACTORS AND RELIGIOUS BELIEFS AS DETERMINANTS OF THE FORMATION OF HEALTHY REPRODUCTIVE CONSCIOUSNESS AMONG YOUTH - Rasulova Nilufar Tulkunovna (Western European Studies, 2025)
The article examines the problem of forming healthy reproductive consciousness among young people in the context of contemporary social transformations. Special attention is paid to the influence of socio-psychological factors, internal personality structures, and social attitudes, as well as to the role of religious beliefs as key determinants of psychological and social stability. The paper provides a detailed analysis of both constructive and destructive religiouspsychological and socio-psychological factors that either facilitate or hinder the formation of healthy reproductive consciousness among youth.
Keywords: reproductive consciousness; youth; socio-psychological factors; religious beliefs